Control of in vitro contamination during the establishment of Pyrus communis explants using Plant Preservative MixtureTM - Grimaldi, Fernanda; Bastos, Fernanda Espíndola Assumpção (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2023)
The presence of fungal and bacterial contamination in in vitro propagation is a determinant of the culture establishment. The biocide PPM (Plant Preservative Mixture™) has been utilized to control in vitro contamination. According to the manufacture’s label, it is a heat-stable, broad-spectrum product, non-selective, that affects directly microorganisms without causing damage to plant cells. The purpose of this study was to evaluate the influence of PPM asepsis on the control of contamination during the in vitro establishment and survival of Pyrus communis rootstock explants. Six compositions were tested for asepsis and explants from two locations (field and greenhouse). The results showed that asepsis with Alcohol 70% (1 minute) + NaOCl 2.5% + Tween 20 (15 minutes), plus 4.0 ml L-1 PPM added to media performed on explants from greenhouse plants and asepsis, with PPM 5% solution bath and PPM 5% solution bath plus 2.0 ml L-1 PPM added to media performed on explants from field-grown plants presented a good microbial control and good rate of survival. Index terms: Biocide; tissue culture; micropropagation; pear tree; PPM.